Frequency analyses of human voice using fast Fourier transform - Mahdi, Jinan F. (Iraqi journal of physics, 2019)
Quantitative analysis of human voice has been subject of interest and the subject gained momentum when human voice was identified as a modality for human authentication and identification. The main organ responsible for production of sound is larynx and the structure of larynx along with its physical properties and modes of vibration determine the nature and quality of sound produced. There has been lot of work from the point of view of fundamental frequency of sound and its characteristics. With the introduction of additional applications of human voice interest grew in other characteristics of sound and possibility of extracting useful features from human voice. We conducted a study using Fast Fourier Transform (FFT) technique to analyze human voice to identify different frequencies present in the voice with their relative proportion while pronouncing selected words like numbers. Details of findings are presented